Questioning Gender: A Comparative Study of Gender Equitable Inheritance Distribution in Indonesia - Potale, Mutiara (Cattleya Darmaya Fortuna, 2024)
This research aims to examine the distribution of gender-equitable inheritance in Indonesia with a qualitative approach using normative and socio-religious methods. The main focus of this research is to analyze gender gaps in inheritance distribution, as well as women's rights from a positive legal perspective. This research is descriptive qualitative in nature and uses a literature review which includes books, scientific articles, journals and related legal documents such as the Civil Code and the Compilation of Islamic Law. The analysis was carried out using thematic analysis techniques to identify main themes regarding the distribution of inheritance and the role of women in the context of Islamic inheritance law and Indonesian positive law. This research also makes a comparison between the two legal systems to explore gender gaps in their implementation. The research results show that gender-equitable distribution of inheritance is strongly influenced by the plurality of society's culture, which is a challenge in realizing a fair inheritance system for women. The main factors that influence equal inheritance rights between men and women include education, migration, economic factors, socio-cultural values, jurisprudence, and individual awakening. However, the customary system that is still dominant in some cultures requires women to follow their husband's clan or family, thus creating inequality in inheritance. It is hoped that this research will provide new insights into inequality in inheritance distribution and offer recommendations for fairer legal policies for women.